Determinants of household food security in rural Bangladesh: an imperial analysis of farm level data - Rahman, KS; Hasan, MK; Hasan, M (Bangladesh Journal of Agricultural Research, 2020)
The study endeavors to estimate the food security status and identify the determinants of food security among households in Hakimpur Upazila in Dinajpur district, Bangladesh. it was found that households of Hakimpur upazila in Dinajpur district were food insecure during the period of the survey. Number of dependents, income of household head, age of household head and level of education were found to significantly influence household head food security in the study area positively. It is recommended that social security measures must ensure that the benefits of public efforts to improve food security and nutrition are universal. Human rights based practices are preferable. Bangladesh J. Agril. Res. 44(4): 649-658, December 2019